Inbreeding effect on quantitative and qualitative specifications of Mulberry silkworm (Damascus University Journal of agriculture sciences, 2026)
The study was carried out at silkworm Laboratory of Agricultural Scientific Research Center of Lattakia, and aimed to improve the quantitative and qualitative specifications of silkworm hybrid Bombyx mori L. Rearing in Syrian coast by inbreeding and family selection. Silkworm hybrid were reared In 2018  at (23-27 °C) and 65-85% R.H., healthy and morphologically similar cocoons were selected and four families were established: Family A (oval cocoons), Family B (waisted cocoons), Family C (elongated cocoons) and Family D (spherical cocoons). Then the offspring were selected within each family based on the weight of the cocoon, shell, and the fecundity rate (egg/female), until reaching the sixth generation (2023 season). The results showed the effectiveness of inbreeding and selection in improving the productive and qualitative characteristics of silkworm families as the generations progressed. The sixth generation of the family A, B was significantly superior in the average weight of larvae, cocoon, pupa, shell, percentage of effectiveness ERR%, fecundity, shell ratio, filament weight, length and denier,.in family A, (6.003g, 1.83g, 1.44g, 0.37g, 93.63% ,709.7 egg/ female, 20.16%, 0.34g, 1500.65m, 2.03denier) respectively, and it was in family B (5.11g, 1.65g, 1.32g, 0.31g, 18.80%, 600.83, egg/ female, 0.28g, 1291.10m, 1.66 denier) respectively. Results also indicated that there were no significant differences in some productive traits in the C and D families as the generations progressed, but it was observed that the sixth generation outperformed, with significant differences, in fertility rate, larval mortality, and development period (661.16 eggs/female, 9.33%, 50.09 Day).
Keywords: Inbreeding, Silkworm, Syria